Youth Organizations as a “Well-arranged” Symbolic Space: An Analysis of the Polish Online Discourse of AIESEC and ATD Fourth World - Violetta Kopińska (SAGE Open)
The symbolic space of an organization can be analyzed as Foucault’s heterotopia and described using his six principles of heterotopia. The premise of this study is that the symbolic space of an organization fulfills the heterotopian compensation function concerning other spaces when trying to balance the world’s complexity by “arranging” it. This article aims to identify the scope of this function in the symbolic space created by online discourses of two youth organizations: AIESEC and ATD Fourth World. The article discusses the results of an analysis of the Polish discourse of these two internationally recognized organizations. Critical Discourse Analysis and a discursive approach to institutions are used for analysis. The material included in the analysis comprised all texts produced in 2018 and published by the organizations on their websites and Facebook accounts in Polish. The research results contribute to knowledge situated at the intersection of research on formalized social activity among youth, research on organizational identities in a critical approach, and organizational identities created online. They demonstrate how youth organizations construct their “offer,” what world “arrangement” they present, and what shortages/problems they tend to highlight in today’s world. Furthermore, in the field of organizational discourse studies, they illustrate how particular ideas defined at the programmatic level can be translated into the discourse of “solutions.”